Juridical Review of Implementation of Immigration Administrative Action in Indonesia (Journal of Governance and Development (JGD), 2020)
It has been nearly a decade since Indonesia had the latest Immigration Act (Law Number 6 of 2011). However, since the new Immigration Act was issued, the implementation of regulations for The Immigration Administrative Action has not yet been established. The purpose of this study is to determine the validity of the implementing regulations of the legislation if the legal basis had been changed and to find out whether the discretion principle can be used as the basis for the procedure of Immigration Administrative Action. The research method used in this study is normative juridical. The conclusion drawn from the research is that the Director General of Immigration Instructions for Implementation Number: F-314.Il.02.10 of 1995 concerning procedures for Immigration Action is still valid but is no longer relevant to the current law, and the use of discretionary authority by the agency Government administration officials can only be done in certain cases where the applicable laws and regulations do not regulate them or because existing regulations governing things are unclear and they are carried out in an emergency or urgent matter for the public interest.